Transport investment and local and regional development: perspectives on the emerging motorway system in Poland - JUDGE, Eamonn (European Spatial Research and Policy, 1999)
The planned Polish motorway programme is argued to have beneficial effects on the local, regional, and national economy. Similar arguments were heard during the development of West European motorway systems. The role of such arguments in the development of the Polish system is examined in the light of the results of current research in the UK. The topic has particular importance in Poland as forecasts of interurban traffic are likely to be insufficient to finance more than limited sections of the proposed toll motorways. Pressure for greater govemmental support for the network means that possible ’non traffic’ justifications for construction are more important.